Growth, productivity and nutrient uptake of barley (Hordeum vulgare) as influenced by different varieties and clipping management - Dhillon, Balwinder Singh; Uppal, R S (Journal of Cereal Research, 2018)
A field experiment was conducted at research farm of Punjab Agricultural University, Ludhiana during winter (rabi) seasons of 2015-16 and 2016-17 to study the effect of different varieties and clipping management on growth, productivity and nutrient uptake of barley (Hordeum vulgare L.). Variety DWRUB 52 produced significantly higher dry-matter, tiller count, grain yield, straw yield and nutrients uptake (N, P, K and Zn) than PL 807 and PL 426, while plant height of this variety was statistically similar with PL 807. Zn foliar spray at anthesis and early milk stage with clipping increased the plant height and dry matter of crop, while clipping alone reduced these growth parameters. Grain yield of control crop was statistically similar with both clipping stages viz. at 50 and 60 DAS. However, there was an increase of 5.7% in the grain yield when clipping was done at 50 DAS over no clipping. Â Clipping at 50 and 60 DAS along with Zn application brought about 13.1 and 8.5% increased the grain yield over control crop. Zn foliar application significantly increased the nitrogen, phosphorous, potassium and zinc nutrients uptake by grain and straw of barley crop than control. Â DOI:10.25174/2249-4065/2018/81019